Effect of detoxification (tadbeer) in content of toxic metabolites of Strychnos nux-vomica: A Unani approach for its use in human - Noman Anwar; Masood Shah Khan; Hifzul Kabir; Sayeed Ahmad (Wolters Kluwer Medknow Publications, 2015)
Background: Azaraqi (Strychnos nux-vomica, Loganiaceae) has been the important Unani medicine since long time as a stimulant, anti-inflammatory, and blood purifier. It has been used very frequently by the Unani practitioner. But the Unani system recommends application of azaraqi in medicine only after its detoxification (tadbeer) may be because of the presence of its deadly poisonous alkaloids (strychnine and brucine). In the present investigation, an attempt has been made to quantify the actual content of their toxic alkaloids before and after the tadbeer. Materials and Methods: A sensitive high-performance thin layer chromatographic (HPTLC) method has been developed for estimation of strychnine and brucine in different samples of azaraqi before and after tadbeer. Precoated HPTLC silica gel plates were used as stationary phase and (toluene: Ethyl acetate: Dietylamine 7:2:1 v/v/v) was used as mobile phase. Result: The Rfvalue of strychnine and brucine was found as 0.53 and 0.41, respectively. Detection and quantification were performed by densitometry at 270 nm. The calibration plot was linear in the range of 50-1000 ng of strychnine and brucine, respectively, with the correlation coefficient (r2) 0.993 and 0.991 for strychnine and brucine, respectively, which confirms good linearity. The content of strychnine was 0.175, 0.07, 0.18, 0.051, and 0.075% w/w whereas brucine was 0.16, 0.117, 0.061, 0.045, and 0.057 in crude azaraqi, azaraqi without outer cover, azaraqi outer cover only, azaraqi mudabbar and azaraqi mudabbar by fried in ghee, respectively. Conclusion: The detoxification results in sharp decrease in content of toxic metabolites. The process by boiling in milk was found much effective but tedious as compare to frying method.